Predictors of metabolic syndrome among adults: a hospital based cross-sectional study - Thombre, Shyam D.; Nakel, Mahavir P.; Hajare, Simran S.; Chavan, Bharat B. (International Journal Of Community Medicine And Public Health, 2026)
Background: Metabolic syndrome (MetS) is a growing public health challenge globally, with particularly high and rising prevalence in rapidly urbanizing nations like India. Characterized by a cluster of interrelated metabolic abnormalities, MetS significantly elevates risk of type 2 diabetes mellitus and cardiovascular disease. Hospital-based prevalence data from tier-2 cities of Maharashtra remain limited. Methods: A hospital-based cross-sectional study was conducted from July to September 2025 among 381 adults (aged ≥18) at the outpatient services of a district hospital ch. Sambhajinagar. Data were collected using a WHO STEPS-based structured questionnaire. Metabolic syndrome was diagnosed by the modified NCEP ATP III criteria with Asia-specific waist circumference thresholds. Data were analysed using SPSS v29; chi-square test and multivariable binary logistic regression were applied; p<0.05 was considered significant. Results: Of 381 participants, 138 (36.22%) fulfilled diagnosis criteria for MetS. Elevated blood pressure, elevated blood glucose, central obesity, raised non-HDL cholesterol and physical inactivity were significantly associated with MetS (p<0.05). On multivariable logistic regression, central obesity (adjusted OR: 48.6), physical inactivity (adjusted OR: 3.21) and elevated non-HDL cholesterol ≥ 130 mg/dl (adjusted OR: 1.74) emerged as independent predictors. Conclusions: The prevalence of MetS was substantially high among hospital outpatients. Central obesity and physical inactivity were the strongest independent predictors. Structured lifestyle modification programmes focusing on physical activity promotion and weight management should be integrated within outpatient services to curb the rising NCD burden.